2006
DOI: 10.1111/j.1463-1326.2006.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference cut‐off points for identification of abdominal obesity among the tunisian adult population

Abstract: Based on the ROC analysis, we suggest a WC of 85 cm for both men and women as appropriate cut-off points to identify central obesity for the purposes of CVD and diabetes-risk detection among Tunisians. WCs of 85 cm in men and 79 cm in women were the most sensitive and specific to identify most subjects with a BMI >/=25 kg/m(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 38 publications
7
45
1
1
Order By: Relevance
“…Similarly, the reported cut-off points for WC range from 102 cm for American men [8], to 94 cm for Europeans [18], 84.5 cm for Omani Arabs [15], and 85 cm for Tunisians [16] and Japanese [9]. The corresponding figures among women are 88 cm for Americans [8], 80 cm for Europeans [10], Omani Arabs [15] and Asians [9], 85 cm for Tunisians [19] and 90 cm for Japanese [9]. For adults in China, the male WC cut-off points is ≥93 cm and female WC is ≥89 cm [14].…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, the reported cut-off points for WC range from 102 cm for American men [8], to 94 cm for Europeans [18], 84.5 cm for Omani Arabs [15], and 85 cm for Tunisians [16] and Japanese [9]. The corresponding figures among women are 88 cm for Americans [8], 80 cm for Europeans [10], Omani Arabs [15] and Asians [9], 85 cm for Tunisians [19] and 90 cm for Japanese [9]. For adults in China, the male WC cut-off points is ≥93 cm and female WC is ≥89 cm [14].…”
Section: Discussionmentioning
confidence: 80%
“…Because the data on waist circumference were not available, for purposes of this analysis, we used the body mass index (BMI) >30 kg/m 2 as a criterion for classifying patients as obese 28, 29, 30. Other large studies have previously used this substitution and showed that there is a strong linear correlation between waist circumference and BMI value 30, 31, 32

Low HDL, defined as <50 mg/dL among women and <40 mg/dL among men.

Elevated fasting plasma triglycerides ≥150 mg/dL.

Elevated systolic blood pressure ≥130 mm Hg, diastolic value ≥85 mm Hg, or treatment of previously diagnosed hypertension.

Elevated fasting plasma glucose ≥100 mg/dL.

…”
Section: Methodsmentioning
confidence: 99%
“…Because the data on waist circumference were not available, for purposes of this analysis, we used the body mass index (BMI) >30 kg/m 2 as a criterion for classifying patients as obese 28, 29, 30. Other large studies have previously used this substitution and showed that there is a strong linear correlation between waist circumference and BMI value 30, 31, 32…”
Section: Methodsmentioning
confidence: 99%
“…Currently such cut-off points are derived from studies among European populations and thus may not be applicable to other ethnic groups. Indeed, some studies suggested that Asian populations manifest CVD risk factors at lower levels of BMI and WC than Westerners, owing, in part, to a higher percentage of body fat 5 14 and 90 cm for Japanese 6 . Differences in cut-off points of obesity have a profound effect on prevalence estimates.…”
Section: Discussionmentioning
confidence: 99%